On equal temperament: Tuning, modernity and compromise. (July 2015) - Halewood, Michael
In this article, I use Stengers' (2010) concepts of 'factish', 'requirements' and 'obligations', as well as Latour's (1993) critique of modernity, to interrogate the rise of Equal Temperament as the dominant system of tuning for western music. I argue that Equal Temperament is founded on an unacknowledged compromise which undermines its claims to rationality and universality. This compromise rests on the standardization which is the hallmark of the tuning system of Equal Temperament, and, in this way, it is emblematic of Latour's definition of modernity. I further argue that the problem of the tuning of musical instruments is one which epitomizes the modern distinction between the natural and the social. In turn, this bears witness to what Whitehead calls the 'bifurcation of nature'. Throughout this article, using the work of Stengers and Latour, I seek to use tuning as a case study which allows social research to talk both of the natural and of the social aspects of music and tuning, without recourse to essentialism or simple social construction. In this way, my argument seeks to avoid bifurcating nature.